2019
DOI: 10.3390/su11164317
|View full text |Cite
|
Sign up to set email alerts
|

A Bidirectional Power Charging Control Strategy for Plug-in Hybrid Electric Vehicles

Abstract: Plug-in Hybrid Electric Vehicles (PHEVs) have the potential of providing frequency regulation due to the adjustment of power charging. Based on the stochastic nature of the daily mileage and the arrival and departure time of Electric Vehicles (EVs), a precise bidirectional charging control strategy of plug-in hybrid electric vehicles by considering the State of Charge (SoC) of the batteries and simultaneous voltage and frequency regulation is presented in this paper. The proposed strategy can control the batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 60 publications
(67 reference statements)
0
50
0
Order By: Relevance
“…The modeling of electricity system consists of active and reactive power nodal balance equations [25]- [26], as shown in (1)…”
Section: A Electricity Systemmentioning
confidence: 99%
“…The modeling of electricity system consists of active and reactive power nodal balance equations [25]- [26], as shown in (1)…”
Section: A Electricity Systemmentioning
confidence: 99%
“…The CE causes significant electrical damages and communication malfunctions in many systems [17][18][19][20][21][22][23][24]. To reduce the CE, there are several methods [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] with different signal attenuation patterns. Each electrical system has different CE characteristics, so the CE attenuation method must be appropriately chosen for each system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Design of robust higher order sliding mode control strategy for hybrid microgrids were discussed by Cucuzzella et al and Baghaee et al [13,14]. Mohammadi et al also reported some works on power management strategy in multi-terminal VSC-HVDC system, adaptive neural observer-based nonsingular terminal sliding mode controller & intelligent controller design for a class of nonlinear systems, bidirectional power charging control strategy for plug-in hybrid EVs for MT-HVDC grids [15][16][17][18][19][20][21][22]. In proposed work, the constant switching SMC is described in which the switching losses are reduced as compared to the primitive SMC by maintaining a constant switching frequency.…”
Section: Introductionmentioning
confidence: 99%